A Side-Channel Protected and High-Performance Hardware Implementation for EdDSA25519 - Pablo Navarro-Torrero; Eros Camacho-Ruiz; Macarena C. Martinez-Rodriguez; Piedad Brox-Jimenez (IEEE Access)
This paper presents a high-performance and secure hardware implementation of the Edwards-Curve Digital Signature Algorithm (EdDSA25519). Using the fixed-base signed multi-comb and the k-ary algorithms for scalar multiplication, the proposed design achieves 307%, 253%, and 48% faster performance in key generation, signature generation, and signature verification, respectively, compared to the fastest previous hardware implementation in the state-of-the-art. When compared to the software-based OpenSSL implementation, our design demonstrates timing performance improvements ranging from 1000% to 2200%. Additionally, we integrate robust Side-Channel Attack (SCA) countermeasures and validate their effectiveness through Test Vector Leakage Assessment (TVLA). The results demonstrate increased resistance to Simple Power Analysis (SPA) and Differential Power Analysis (DPA), offering a hardware-based secure solution for modern cryptographic applications.